Circ_0124644 Serves as a ceRNA for miR-590-3p to Promote Hypoxia-Induced Cardiomyocytes Injury via Regulating SOX4 - Tan, Juan; Pan, Weinan; Chen, Huilin; Du, Yafang; Jiang, Peiyong; Zeng, Dianmei; Wu, Jie; Peng, Kuang (Frontiers in Genetics, 2021)
Circular RNA (circRNA) is an important factor for regulating the progression of many cardiovascular diseases, including acute myocardial infarction (AMI). However, the role of circ_0124644 in AMI progression remains unclear. Hypoxia was used to induce cardiomyocytes injury. The expression of circ_0124644, microRNA (miR)-590-3p and SRY-box transcription factor 4 (SOX4) mRNA was measured by qRT-PCR. Cell counting kit 8 (CCK8) assay and flow cytometry were utilized to detect cell viability, cell cycle progression and apoptosis. The protein levels of apoptosis markers and SOX4 were determined by western blot (WB) analysis, and the levels of oxidative stress markers were assessed using commercial Assay Kits. Dual-luciferase reporter assay, RIP assay and RNA pull-down assay were employed to confirm the interaction between miR-590-3p and circ_0124644 or SOX4. Circ_0124644 was upregulated in AMI patients and hypoxia-induced cardiomyocytes. Hypoxia could inhibit cardiomyocytes viability, cell cycle process and promote apoptosis and oxidative stress, while silencing circ_0124644 could alleviate hypoxia-induced cardiomyocytes injury. In terms of mechanism, circ_0124644 could target miR-590-3p. MiR-590-3p overexpression could relieve hypoxia-induced cardiomyocytes injury. Also, the suppressive effect of circ_0124644 knockdown on hypoxia-induced cardiomyocytes injury could be reversed by miR-590-3p inhibitor. Moreover, SOX4 was found to be a target of miR-590-3p, and its overexpression also could reverse the regulation of miR-590-3p on hypoxia-induced cardiomyocytes injury. Circ_0124644 silencing could alleviate hypoxia-induced cardiomyocytes injury by regulating the miR-590-3p/SOX4 axis, suggesting that it might be a target for alleviating AMI.